The influence of health education using herbal e-catalog media and conventional education community knowledge and interest in the use of toga as a tradisonal medicine for self-medication - Octavia, Devi Ristian; Utami, Primanitha Ria (Alma Ata University Press, 2024)
Background: Inappropriate use of medicines in self-medication practice will cause drug-related problems due to limited knowledge about drugs and their use. Family medicinal plants (TOGA) can be an alternative to traditional medicine for safer self-medication practices.Objectives: This research aims to analyze the influence of health education using herbal e-catalogue media in increasing public knowledge and interest regarding the use of family medicinal plants (herbs) for rational self-medication practices.Methods: The design of this research is Quasi Experimental with a pretest-posttest control group design. Knowledge measurements were carried out twice, namely before the intervention and three weeks after the intervention. The intervention was carried out 3 times with an interval of one week. The sampling technique is purposive sampling. The instrument used in the research was a validated questionnaire. Data analysis to see differences in scores of people's knowledge and interest in using herbs for self-medication in the treatment group and control group was analyzed using the Wilcoxon test. To see the effect of using the Herbal e-catalog media, analysis was carried out using the Mann-Whitney test.Results: The research results showed that there was a significant difference in the pretest and posttest results in the control group and intervention group with a value (p value = 0.000), but there was no difference in knowledge about the use of herbs for self-medication in the two groups (p value = 0.664).Conclusions: Health workers need to provide education to the public so that public knowledge about the use of traditional medicine in self-medication practices can provide the expected therapeutic results.